ASSOCIATIONS OF GH AND IGF1R GENE POLYMORPHISM WITH AVARAGE DAILY GAIN AND BODY MEASUREMANT IN PESISIR CATTLE (Prosiding Seminar Teknologi dan Agribisnis Peternakan (STAP), 2018)
The objectives of the present study were to investigate the genetic variability of the GH/AluI, GH/MBoII and IGF1R/MspI  in Pesisir cattle and to analyze their effect on average daily gain and body measurement such as body lenght, chest girth, height withers. Total  175 Pesisir Cattles were used in this research. Weight gain, and body measurement were fitted using the General Linear Model (GLM) procedure of the SAS program. The results showed significant associations between GH/MBoII and IGF1R/MspI polymorphism with weight gain and height withers (p < 0.05). The effect of GH/AluI polymorphisms  was not observed on average daily gain and body measurement in Pesisir cattle (P>0.05). The results demostrated that the GH/MBoII and IGF1R/MSpI  polymorphisms could be used as a candidate gene for selection in Pesisir cattle.Key words: Pesisir cattle, GH/MBoII, GH/AluI, IGF1R/MspI polymorphism, RFLP, avarage daily gain,  body measurement.